2001
DOI: 10.1042/0264-6021:3600087
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II inhibits insulin-stimulated phosphorylation of eukaryotic initiation factor 4E-binding protein-1 in proximal tubular epithelial cells

Abstract: Interaction between angiotensin II, which binds a G-protein-coupled receptor, and insulin, a ligand for receptor tyrosine kinase, was examined in renal proximal tubular epithelial cells. Augmented protein translation by insulin involves activation of eukaryotic initiation factor 4E (eIF4E) which follows the release of the factor from a heterodimeric complex by phosphorylation of its binding protein, 4E-BP1. Angiotensin II (1 nM) or insulin (1 nM) individually stimulated 4E-BP1 phosphorylation. However, pre-inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 35 publications
3
21
0
Order By: Relevance
“…In agreement with the above schema, ANG II stimulated important events in capdependent translation including phosphorylation of 4E-BP1 and eIF4E. Our studies in MCT cells have shown that phosphorylation of 4E-BP1 by ANG II is associated with dissolution of the eIF4E-4E-BP1 complex (43). The inability of ANG II to induce VEGF expression in cells expressing 4E-BP1 phosphorylation mutant further confirmed cap-dependent translation as the underlying mechanism.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…In agreement with the above schema, ANG II stimulated important events in capdependent translation including phosphorylation of 4E-BP1 and eIF4E. Our studies in MCT cells have shown that phosphorylation of 4E-BP1 by ANG II is associated with dissolution of the eIF4E-4E-BP1 complex (43). The inability of ANG II to induce VEGF expression in cells expressing 4E-BP1 phosphorylation mutant further confirmed cap-dependent translation as the underlying mechanism.…”
Section: Discussionsupporting
confidence: 74%
“…5C, P Ͻ 0.01). We previously showed that ANG II promotes dissociation between eIF4E and 4E-BP1 under these experimental conditions in MCT cells (43). These data demonstrate that ANG II regulates events of regulatory significance in the initiation phase of translation.…”
Section: Ang II Increases Vegf Protein But Not Mrna In Mct Cellsmentioning
confidence: 82%
See 2 more Smart Citations
“…Protein synthesis measurement was as previously described (49). Serum-starved cells were labeled with 10 Ci/ml of [ 35 S]methionine for the terminal 2 h of incubation.…”
Section: Methodsmentioning
confidence: 99%